Obytný dům - Staňková, Pavla (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Předmětem této bakalářské práce je návrh obytného domu. Stavební objekt se nachází severovýchodním okraji města Boskovice. Pozemek vybraný pro stavbu je situován v katastrálním území Boskovice. Objekt je řešen jako samostatně stojící, se dvěma nadzemními podlažími, nepodsklepený. Obytný dům je určen pro bydlení. Jsou zde navrženy 4 byty. Každý byt je doplněn garáží uvnitř objektu. Vstup do objektů je ze severozápadní strany pozemku. Obvodové zdivo domu bude provedeno z keramických tvárnic Porotherm 30 Profi. Stropní konstrukce je ze železobetonových předpjatých stropních panelů SPIROLL. Obytný dům je zastřešen plochou jednoplášťovou vegetační střechou.

The subject of this bachelor thesis is the design of a residential building. The building is situated on the northeastern outskirts of Boskovice. The land selected for construction is located in the cadastral area of Boskovice. The object is solved as stand-alone, with two above-ground floors, without basement. Residential house is designed for housing. There are 4 apartments. Each apartment is complemented by a garage inside the building. The entrance to the buildings is from the northwest side of the property. The perimeter of the house will be made of Porotherm 30 Profi ceramic blocks. The ceiling structure is made of reinforced concrete prestressed ceiling panels SPIROLL. The residential building is covered with a flat, single-skinned vegetation roof.
Residential house
Keywords: Obytný dům; novostavba; vegetační střecha; plochá střecha; keramické tvárnice Porotherm.; Residential building; new building; vegetation roof; flat roof; ceramic Porotherm.